2017
DOI: 10.1371/journal.pone.0185179
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the ability to maintain balance as a result of stochastic resonance whole body vibration in women

Abstract: PurposeA vertical posture makes it difficult to maintain balance especially in the elderly. Loss of balance leads to falls and injuries. In the present study, we evaluated whether balance maintenance can be improved with the use of stochastic resonance whole body vibration (SR-WBV).MethodsAn examination of balance, involving 187 women aged 19–74 years, was conducted using double-plate posturography pre and post SR-WBV. The SR-WBV trainings were performed using the SRT Zeptor Medical-plus noise device. The enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Similarly, Rogan and Herren et al [17,18] demonstrated an improvement in functional muscle strength after the SR-WBV intervention in less active older adults. SR-WBV was also shown to play a role in improving women's ability to maintain balance [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rogan and Herren et al [17,18] demonstrated an improvement in functional muscle strength after the SR-WBV intervention in less active older adults. SR-WBV was also shown to play a role in improving women's ability to maintain balance [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that stochastic vibrations are an effective way to improve walking, coordination, posture, and manual performance in patients with locomotive diseases [10]. Donocik et al [11] performed SR-WBV training (frequency: 2-8 Hz; amplitude: 0.5-3.5 mm; duration: 6 weeks, 2 times a week) in women and showed the improvement in maintaining balance and postural control. Stochastic vibrations (frequency: 3-6 Hz; amplitude: 4 mm; level of noise: 4; duration: 8 weeks) also contribute to muscle strength and bone structure improvement [12], which can affect bone density, physical fitness, and improve comfort in an individual's general life [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of scientific reports show a positive effect of physical activity on body composition [2]. In the literature, we can also find evidence of the positive impact of vibrations with stochastic resonance on other aspects of the human body, e.g., balance, muscle pain, and cognitive functions [9][10][11]. The impact of stochastic resonance whole body vibrations on individual parameters of female body composition have never been studied before.…”
Section: Introductionmentioning
confidence: 87%
“…Recent data demonstrate that it is also impossible to exclude the fact that researchers generally evaluate the effectiveness of laser therapy based only on imperfect tests (e.g., Lasàgue's or Schober's) and questionnaires in terms of measurement error. In addition, the questionnaires used analyze only subjective (i.e., indicated by the patient) pain sensations as well as functional abilities and disturbances in mobility (116,12–14).…”
Section: Introductionmentioning
confidence: 99%
“…Computerized posturography testing is a valuable and objective technique for measuring postural strategies under challenging static and dynamic conditions (15). The strategy allows assessment of balance control with highly repeatable measurements, which determines the efficiency of the balance and proprioception systems, especially the coordination functions of the nervous and muscular systems (16). Proprioception participates in the maintenance of a standing posture of the body by constantly regulating center of pressure (COP) movements necessary for orthogonal projection of the center of gravity (COG) during the postural phase (17).…”
Section: Introductionmentioning
confidence: 99%